2008 Winter Simulation Conference 2008
DOI: 10.1109/wsc.2008.4736091
|View full text |Cite
|
Sign up to set email alerts
|

Data enhancement, smoothing, reconstruction and optimization by kriging interpolation

Abstract: The performance of Kriging interpolation for enhancement, smoothing, reconstruction and optimization of a test data set is investigated. Specifically, the ordinary twodimensional Kriging and 2D line Kriging interpolation are investigated and compared with the well-known digital filters for data smoothing. We used an analytical 2D synthetic test data with several minima and maxima. Thus, we could perform detailed analyses in a well-controlled manner in order to assess the effectiveness of each procedure. We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…This contrasts to other forms such as simple kriging and universal kriging, which use a known constant trend value or a trend function, respectively, in their modeling assumptions. Researchers have made comparisons of the performance of these kriging models, and they have shown that universal kriging generally provides better results in cases where the underlying trend is understood and can be adequately captured (Zimmerman et al, 1999; Altman, 2000; Gunes et al, 2008). Within the context of structural deformations, it is possible to estimate the underlying trend of point cloud data in such cases as elastic flexure of beams.…”
Section: Methodsmentioning
confidence: 99%
“…This contrasts to other forms such as simple kriging and universal kriging, which use a known constant trend value or a trend function, respectively, in their modeling assumptions. Researchers have made comparisons of the performance of these kriging models, and they have shown that universal kriging generally provides better results in cases where the underlying trend is understood and can be adequately captured (Zimmerman et al, 1999; Altman, 2000; Gunes et al, 2008). Within the context of structural deformations, it is possible to estimate the underlying trend of point cloud data in such cases as elastic flexure of beams.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in [6], the methods are used to estimate the average magnitude of the electromagnetic field in a pilot area in Caracas, Venezuela. In [7], kriging is used to smooth and enhance noisy data as well as construct missing data. In [8], inverse distance weighting is used in the determination of the geoclimatic factor for South Africa.…”
Section: Interpolationmentioning
confidence: 99%
“…These methods are spatial in that they assume data continuity over space which allows the prediction of a variable at any location within a particular boundary [6]. Kriging depends on the spatial and statistical interdependence of data values to make predictions by employing semivariogram modeling [7]. IDW, on the other hand, uses the simple metric distance weights to make predictions and is therefore a simpler and faster method for few data points [8].…”
Section: Introductionmentioning
confidence: 99%
“…While many studies investigate the reconstruction of environmental factors like sea surface temperature (SST) (Bignami et al, 2007;Zhao and He, 2012;Shropshire et al, 2016;Ji et al, 2018;Ma et al, 2021), wind field (Jayaram et al, 2014), turbidity (Alvera-Azcaŕate et al, 2015), sea surface salinity (SSS) (Alvera-Azcaŕate et al, 2016), and total suspended matter (NeChad et al, 2011)in ocean-color remote sensing, reconstruction methods for chlorophyll-a concentration data, crucial for global climate change and biogeochemical cycles, remain underdeveloped and warrant further exploration (Gunes et al, 2008;NeChad et al, 2011;Waite and Mueter, 2013). Most studies focus on regions with fewer missing data, such as the Mediterranean Sea (Alvera-Azcaŕate et al, 2005;Beckers et al, 2006;Antoine et al, 2008;Brando et al, 2015), the northern South China Sea (Ping et al, 2016;Ma et al, 2021), and the North Atlantic Ocean (Everson et al, 1996;Iida and Saitoh, 2007;Xiu et al, 2007;Zhao and He, 2012;Jouini et al, 2013;Waite and Mueter, 2013;Li and He, 2014;Wang and Liu, 2014;Liu and Wang, 2016;Shropshire et al, 2016;Hilborn and Costa, 2018;Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%